/- Copyright (c) 2019 Simon Hudon. All rights reserved. Released under Apache 2.0 license as described in the file LICENSE. Authors: Simon Hudon, Yury Kudryashov -/ import data.list.big_operators /-! # Free monoid over a given alphabet ## Main definitions * `free_monoid α`: free monoid over alphabet `α`; defined as a synonym for `list α` with multiplication given by `(++)`. * `free_monoid.of`: embedding `α → free_monoid α` sending each element `x` to `[x]`; * `free_monoid.lift`: natural equivalence between `α → M` and `free_monoid α →* M` * `free_monoid.map`: embedding of `α → β` into `free_monoid α →* free_monoid β` given by `list.map`. -/ variables {α : Type*} {β : Type*} {γ : Type*} {M : Type*} [monoid M] {N : Type*} [monoid N] /-- Free monoid over a given alphabet. -/ @[to_additive "Free nonabelian additive monoid over a given alphabet"] def free_monoid (α) := list α namespace free_monoid @[to_additive] instance : monoid (free_monoid α) := { one := [], mul := λ x y, (x ++ y : list α), mul_one := by intros; apply list.append_nil, one_mul := by intros; refl, mul_assoc := by intros; apply list.append_assoc } @[to_additive] instance : inhabited (free_monoid α) := ⟨1⟩ @[to_additive] lemma one_def : (1 : free_monoid α) = [] := rfl @[to_additive] lemma mul_def (xs ys : list α) : (xs * ys : free_monoid α) = (xs ++ ys : list α) := rfl /-- Embeds an element of `α` into `free_monoid α` as a singleton list. -/ @[to_additive "Embeds an element of `α` into `free_add_monoid α` as a singleton list." ] def of (x : α) : free_monoid α := [x] @[to_additive] lemma of_def (x : α) : of x = [x] := rfl @[to_additive] lemma of_injective : function.injective (@of α) := λ a b, list.head_eq_of_cons_eq /-- Recursor for `free_monoid` using `1` and `of x * xs` instead of `[]` and `x :: xs`. -/ @[elab_as_eliminator, to_additive "Recursor for `free_add_monoid` using `0` and `of x + xs` instead of `[]` and `x :: xs`."] def rec_on {C : free_monoid α → Sort*} (xs : free_monoid α) (h0 : C 1) (ih : Π x xs, C xs → C (of x * xs)) : C xs := list.rec_on xs h0 ih @[ext, to_additive] lemma hom_eq ⦃f g : free_monoid α →* M⦄ (h : ∀ x, f (of x) = g (of x)) : f = g := monoid_hom.ext $ λ l, rec_on l (f.map_one.trans g.map_one.symm) $ λ x xs hxs, by simp only [h, hxs, monoid_hom.map_mul] /-- Equivalence between maps `α → M` and monoid homomorphisms `free_monoid α →* M`. -/ @[to_additive "Equivalence between maps `α → A` and additive monoid homomorphisms `free_add_monoid α →+ A`."] def lift : (α → M) ≃ (free_monoid α →* M) := { to_fun := λ f, ⟨λ l, (l.map f).prod, rfl, λ l₁ l₂, by simp only [mul_def, list.map_append, list.prod_append]⟩, inv_fun := λ f x, f (of x), left_inv := λ f, funext $ λ x, one_mul (f x), right_inv := λ f, hom_eq $ λ x, one_mul (f (of x)) } @[simp, to_additive] lemma lift_symm_apply (f : free_monoid α →* M) : lift.symm f = f ∘ of := rfl @[to_additive] lemma lift_apply (f : α → M) (l : free_monoid α) : lift f l = (l.map f).prod := rfl @[to_additive] lemma lift_comp_of (f : α → M) : (lift f) ∘ of = f := lift.symm_apply_apply f @[simp, to_additive] lemma lift_eval_of (f : α → M) (x : α) : lift f (of x) = f x := congr_fun (lift_comp_of f) x @[simp, to_additive] lemma lift_restrict (f : free_monoid α →* M) : lift (f ∘ of) = f := lift.apply_symm_apply f @[to_additive] lemma comp_lift (g : M →* N) (f : α → M) : g.comp (lift f) = lift (g ∘ f) := by { ext, simp } @[to_additive] lemma hom_map_lift (g : M →* N) (f : α → M) (x : free_monoid α) : g (lift f x) = lift (g ∘ f) x := monoid_hom.ext_iff.1 (comp_lift g f) x /-- The unique monoid homomorphism `free_monoid α →* free_monoid β` that sends each `of x` to `of (f x)`. -/ @[to_additive "The unique additive monoid homomorphism `free_add_monoid α →+ free_add_monoid β` that sends each `of x` to `of (f x)`."] def map (f : α → β) : free_monoid α →* free_monoid β := { to_fun := list.map f, map_one' := rfl, map_mul' := λ l₁ l₂, list.map_append _ _ _ } @[simp, to_additive] lemma map_of (f : α → β) (x : α) : map f (of x) = of (f x) := rfl @[to_additive] lemma lift_of_comp_eq_map (f : α → β) : lift (λ x, of (f x)) = map f := hom_eq $ λ x, rfl @[to_additive] lemma map_comp (g : β → γ) (f : α → β) : map (g ∘ f) = (map g).comp (map f) := hom_eq $ λ x, rfl end free_monoid